Enhancing Landslide Early Warning: Advances in Fiber Optic Sensor Sensitivity - Fatimah Nur Hidayah; Haikal; Budi Nur C. E. B; Zuhdi Ismail (Multidisciplinary Innovations and Research in Applied Engineering, 2024)
Fiber optic sensors offer a high-performance alternative because they provide a low-cost solution, resistance to electromagnetic interference, multiplexing capabilities, and high integration. The performance of fiber optic sensors applies to measuring physical parameters such as pressure, bending, and temperature. This study aims to determine the optimal value of using optical fiber types in landslide early detection sensors. The method used is bending in the form of deflection on the optical fiber. The deflection values used are 0 mm - 15 mm, 0 mm - 20 mm, and 0 mm - 25 mm. The optical fiber is placed horizontally in the middle of the bending tool. This bending affects the deflection of the optical fiber, resulting in the attenuation of light in the optical fiber. The deflection phenomenon results in light attenuation in the optical fiber. The sensitivity level of a single-mode fiber optic sensor is higher than a multimode. It shows the greater linearity value in each deflection treatment. Single-mode optical fiber linearity data on deflection variations of 0 - 15 mm, 0 - 20 mm, and 0 - 25 mm, respectively, are 0.9833, 0.9871, and 0.9847. At the same time, the linearity data of multimode optical fiber is 0.8926, 0.9841, and 0.9687. Single-mode optical fiber is more sensitive than multimode optical fiber. It is caused by the core diameter of single-mode optical fiber, which is much smaller than that of multimode optical fiber. The difference in core diameter results in differences in light propagation in the optical fiber. The small diameter of the core has a low dispersion level so that more light intensity is reflected into the core. Light attenuation occurs in a single-mode optical fiber due to macro bending treatment. Meanwhile, the attenuation of light in Multimode fiber optics is due to the bending and dispersion of light. Therefore, a landslide early detection sensor design is more optimal by using a single-mode optical fiber.